The Role of Brand Equity in Strengthening the Competitiveness of “Dinara Wooden Heel” Batik Sandal Products - Rif’atul Khusnia; Sudarmiatin Sudarmiatin; Agus Hermawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the role of brand equity in enhancing the competitiveness of batik sandal products at “Dinara Wooden Heel.” The research adopts a qualitative approach using a case study method to gain an in-depth understanding of how the elements of brand equity namely brand awareness, perceived quality, brand association, and brand loyalty are developed and utilized by the business actors. Data were collected through in-depth interviews with the business owner and consumers, direct observation, and documentation. The data analysis technique was conducted descriptively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that brand equity plays a significant role in improving the competitiveness of Dinara Wooden Heel. The dimensions of perceived quality and brand association serve as the primary strengths in creating competitive advantage through consistent product quality and culture-based differentiation. Meanwhile, brand awareness declined due to distribution limitations during the pandemic, but has gradually recovered through the utilization of social media. On the other hand, brand loyalty has been established through repeat purchases, although its management remains relatively informal. Overall, the four dimensions of brand equity are integrated in enhancing competitiveness through brand visibility, product differentiation, consumer trust, and customer loyalty.